Initial combination therapy with metformin, pioglitazone and exenatide is more effective than sequential add‐on therapy in subjects with new‐onset diabetes. Results from the Efficacy and Durability of Initial Combination Therapy for Type 2 Diabetes (EDICT): a randomized trial. Issue 3 (7th January 2015) - Abdul‐Ghani, M. A.; Puckett, C.; Triplitt, C.; Maggs, D.; Adams, J.; Cersosimo, E.; DeFronzo, R. A
<x xml:space="preserve">Abstract</x> Aim To test our hypothesis that initiating therapy with a combination of agents known to improve insulin secretion and insulin sensitivity in subjects with new‐onset diabetes would produce greater, more durable reduction in glycated haemoglobin (HbA1c) levels, while avoiding hypoglycaemia and weight gain, compared with sequential addition of agents that lower plasma glucose but do not correct established pathophysiological abnormalities. Methods Drug‐naïve, recently diagnosed subjects with type 2 diabetes mellitus (T2DM) were randomized in an open‐fashion design in a single‐centre study to metformin/pioglitazone/exenatide (triple therapy; n = 106) or an escalating dose of metformin followed by sequential addition of sulfonylurea and glargine insulin (conventional therapy; n = 115) to maintain HbA1c levels at <6.5% for 2 years. Results Participants receiving triple therapy experienced a significantly greater reduction in HbA1c level than those receiving conventional therapy (5.95 vs. 6.50%; p < 0.001). Despite lower HbA1c values, participants receiving triple therapy experienced a 7.5‐fold lower rate of hypoglycaemia compared with participants receiving conventional therapy. Participants receiving triple therapy experienced a mean weight loss of 1.2 kg versus a mean weight gain of 4.1 kg (p < 0.01) in those receiving conventional therapy. Conclusion The results of this exploratory study show that combination therapy with metformin/pioglitazone/exenatide in patients with newly diagnosed T2DM is more effective and results in fewer hypoglycaemic events than sequential add‐on therapy with metformin, sulfonylurea and then basal insulin.